Legal Protection for Cryptocurrency Holders as a Means of Conducting Transactions in the Digital Age - Robby Robby; Puguh Aji Hari Setiawan; Dewi Iryani (International Journal Labs, 2026)
The problem in this research is about the binding power of the use of cryptocurrencies in electronic business transactions as a medium for buying and selling transactions. Meanwhile, money in Islam is the same as the currency that is determined in the policy in Indonesia, namely it has value, is generally accepted, and has a certain type that has been determined. In addition, what is called a legal medium of exchange is only recognized as an asset, not a legal currency in Indonesia. This research uses a normative legal (library-based) approach with a statute approach to analyze legal regulations for crypto asset owners in conducting digital transactions in Indonesia. Based on the results of the research, it is known that there are differences between policy provisions electronic transactions and currency laws as well as the provisions of the Civil Code. The difference that exists occurs in business transactions using cryptocurrencies as currency in buying and selling transactions in the digital era using the internet network. The use of crypto does not have binding force in even though the terms and pillars of the agreement have been met. because it still contains elements of gharar, dharar and qimar in accordance with the opinions of the scholars and hasik of the 7th MUI Ijtima Ulama Year 2021. Therefore, their use as a medium of exchange is considered prohibited and lacks legal protection under Indonesian law.